Key innovations and the diversification of Hymenoptera - Bonnie B. Blaimer; Bernardo F. Santos; Astrid Cruaud; Michael W. Gates; Robert R. Kula; István Mikó; Jean-Yves Rasplus; David R. Smith; Elijah J. Talamas; Seán G. Brady; Matthew L. Buffington (Nature Communications, 2023)
Hymenoptera is an incredibly diverse order, with numerous behavioral and morphological innovations. Here, the authors compile a time-calibrated Hymenoptera phylogeny and find that secondary transitions to phytophagy, plant feeding, are associated with significant increases in diversification rate in this group.